Controlling Immigration Manually: Lessons from Moscow (Russia) - Schenk, Caress (My University, 2013)
In 2007, the Russian government instituted quotas for immigrant work permits that were consistently lower than actual labour demand. While low quotas are politically popular on the mass level, this article argues that low quotas are also a tool of the government to distribute patronage resources to regional political and economic elites. For several years after quotas were instituted, they remained quite controversial, and during this time decisions about them were firmly in the hands of Vladimir Putin, first as president and then as prime minister, giving him a powerful tool to control the immigration process and labour market manually. While this type of manual control is effective in the short term to manage contentious policy arenas, it suffers a number of possible long-term consequences.
Keywords: Europe-Asia Studies; Russia; Immigration